SOX10 Single Transcription Factor-Based Fast and Efficient Generation of Oligodendrocytes from Human Pluripotent Stem Cells. - García-León, Juan Antonio; Kumar, Manoj; Boon, Ruben; Chau, David; One, Jennifer; Wolfs, Esther; Eggermont, Kristel; Berckmans, Pieter; Gunhanlar, Nilhan; de Vrij, Femke; Lendemeijer, Bas; Pavie, Benjamin; et al. (Elsevier, 2018)
Scarce access to primary samples and lack of efficient protocols to generate oligodendrocytes (OLs) from human pluripotent stem cells (hPSCs) are hampering our understanding of OL biology and the development of novel therapies. Here, we demonstrate that overexpression of the transcription factor SOX10 is sufficient to generate surface antigen O4-positive (O4+) and myelin basic protein-positive OLs from hPSCs in only 22 days, including from patients with multiple sclerosis or amyotrophic lateral sclerosis. The SOX10-induced O4+ population resembles primary human OLs at the transcriptome level and can myelinate neurons in vivo. Using in vitro OL-neuron co-cultures, myelination of neurons by OLs can also be demonstrated, which can be adapted to a high-throughput screening format to test the response of pro-myelinating drugs. In conclusion, we provide an approach to generate OLs in a very rapid and efficient manner, which can be used for disease modeling, drug discovery efforts, and potentially for therapeutic OL transplantation.
Keywords: Esclerosis múltiple; iPSC; multiple sclerosis; Alzheimer; oligodendrocyte